2021
DOI: 10.1364/oe.422493
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear modulation on optical trapping in a plasmonic bowtie structure

Abstract: Surface plasmon optical tweezers based on micro- and nano-structures are capable of capturing particles in a very small spatial scale and have been widely used in many front research fields. In general, distribution of optical forces and potential wells exerted on the particles can be modulated by controlling the geometric parameters of the structures. However, these fabricated structures are irreversible once processed, which greatly limits its application in dynamic manipulation. The plasmonic field in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This work can deepen the understanding of spin−orbit coupling in time-varying plasma fields, and provide new ideas for light-matter interaction, particle trapping and ultrafast on-chip optical information processing. For example, some previous works have proved that both the femtosecond laser and SPP fields can be used in nonlinear optical tweezers [44][45][46], here the femtosecond SPP vortex field could also enhance the nonlinear optical response of nanoparticles and control the nonlinear motion of nanoparticles. In ultrafast optical information processing, some previous works have demonstrated that ultrafast time-varying effects induced by two time-delayed femtosecond pulses can be used in the fields of optical switching, time-varying holographic imaging, and beam modulation.…”
Section: Discussionmentioning
confidence: 99%
“…This work can deepen the understanding of spin−orbit coupling in time-varying plasma fields, and provide new ideas for light-matter interaction, particle trapping and ultrafast on-chip optical information processing. For example, some previous works have proved that both the femtosecond laser and SPP fields can be used in nonlinear optical tweezers [44][45][46], here the femtosecond SPP vortex field could also enhance the nonlinear optical response of nanoparticles and control the nonlinear motion of nanoparticles. In ultrafast optical information processing, some previous works have demonstrated that ultrafast time-varying effects induced by two time-delayed femtosecond pulses can be used in the fields of optical switching, time-varying holographic imaging, and beam modulation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, near-filed optical devices have attracted attention as a means of handling smaller particles by overcoming the diffraction limit and transporting tiny particles in flexible trajectories. As a result, waveguides, such as nanosized optical fibers, photonic crystal resonators, slot waveguides [11,12], V groove waveguides [13], and nanoapertures [9,10], have become research targets. Yang analyzed the optical transport and trapping of gold and polystyrene nanoparticles smaller than 100 nm in silicon slot waveguides [11].…”
Section: Introductionmentioning
confidence: 99%
“…The method of using the high-intensity laser to enhance the optical force and the limitation of the diffraction limit, and ensuing thermal effects and lack of capture accuracy which greatly restricts its manipulation for nanoscale objects [3][4][5][6][7]. Fortunately, the ability of metal nanostructures to limit light at the subwavelength scale provides new opportunities for the manipulation of nanoscale objects, the OT based on plasmonic substrates has also been developed and named plasmonic optical tweezer (POT) [1,2,[8][9][10][11][12]. POT does not require complex laser focusing equipment [13], and the optical force is caused by the optical gradient force enhanced by the local electromagnetic field excited in the plasmonic nanostructure [1,8,14].…”
Section: Introductionmentioning
confidence: 99%